Modification of the Role of a Teacher Under the Conditions of Distance Learning - Ekaterina Viktorovna Otts (Kassel University Press, 2021)
The article examines the features of the transformation of the role of a teacher in higher education in connection with the digitalization of education in the period before the pandemic, and during the transition of the university to a forced remote mode under the conditions of the pandemic. The assessment of the effectiveness of distance learning from the point of view of students and teachers is given. The purpose of the article is to determine expectations, the degree and nature of the influence of the teacher's personality on the effectiveness of educational process in general and distance learning in particular. Researching the effectiveness of higher education in the digital age and assessing the impact on teacher effectiveness involves the use of a number of scientific principles and research methods, theoretical and empirical. To achieve the goal, the scientific works of leading foreign and Russian scientists on the problems of digitalization of education, dehumanization of education, transformation of the role of the teacher have been analyzed, and our own research has been carried out on the basis of the Moscow Polytechnic University in the form of a survey. An assessment of the emotional consequences of isolation is given. The analysis of the effectiveness of distance learning, from the point of view of higher education teachers and students has been carried out. The expectations of students and the change in the role of a teacher of higher education as a result of expansion of functional responsibilities under the circumstances of distance learning are described. Long before the coronavirus pandemic, digitalization had been a trend in the education system. A year of distance learning has revolutionized higher education. The role of a teacher in higher education has been transformed with a significant expansion of functions and a rapid increase in the level of competencies.